Analysis and optimization of a double-sided air-cored tubular generator - Guo, Liang; Zhang, He; Lin, Jing; Galea, Michael; Gerada, C. (Institute of Electrical and Electronics Engineers, 2015)
In this paper, the design and development of a double-sided air-cored tubular generator (DSTG) is presented. The characteristics of air-cored slot-less structures are investigated in terms of power density and efficiency. This is highly desirable for small- and medium-sized renewable energy conversion systems. In this paper, an analytical tool based on the magnetic vector potential method is built in order to achieve a fast but accurate method by which the machine is analyzed. The analytical model is validated by finite-element (FE) analysis. Further design improvements based on the analytical and FE models are then suggested in order to enhance the performance of the DSTG. The final design of the DSTG is validated by the test results from a developed prototype of the DSTG.